(untitled) (KULT_online, 2009)
April 2006 marked the third joint conference of ARD, ZDF and the broadcast departments of the Protestant and Catholic Churches, whose goal was to assess current research on fostering media literacy and define directions for the future. The volume Medienkompetenz. Zauberwort oder Leerformel des Jugendmedienschutzes (Media Literacy: Magic Words, or Empty Phrase of Public Protection Laws?) documents the results in a range of formats, from lecture transcriptions to workshop outcome summaries. Regretably, the anthology lacks both a unifying concept and a well-defined target audience, and will likely disappoint readers with either a scholarly or practical interest in the issue.